Dampak European Green Deal terhadap Kesejahteraan Petani dan Ketahanan Pangan di Eropa - Safira Nadhila Firdhausa (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
The European Green Deal is the European Union's strategy to reduce the impact of climate change and carry out major reforms in the agricultural sector. However, small and medium-sized farmers are suffering losses due to shift to more environmentally friendly agricultural system, stricter regulations, reduced subsidies, and restrictions on chemical fertilizers. In this journal, it can be seen how EGD policies create economic and social vulnerabilities that could threaten food security and the internal stability of the European Union. The methods used are a qualitative approach and descriptive analysis of the impact of green deal policies, which affect farmers and the general public. Data collection was conducted through a literature review of previous studies related to the impacts of the Green Deal. This journal discusses four key areas, the transformation of Green Deal policies, economic vulnerabilities faced by farmers, emerging social-political resistance, and implications for non-traditional security. The research indicates that while EGD policies aim to address climate threats, their implementation has led to non-security issues. A balance between climate and long-term food security is needed. To address social and economic changes at the domestic and regional levels, this study emphasizes the importance of inclusive and adaptive green transition policies.